Augmented Reality-Based Learning Media to Improve Student Motivation and Learning Outcomes - FIRMANSYAH, MUHAMMAD HAFIDH; Azhar, Alivia (SAINTEKBU, 2024)
With the rapid advancement of information technology, it does not necessarily correlate with an equally swift increase in students' interest in the learning experience. Students need proper guidance in the use of information technology to enhance their learning interest, and one type of technology that can be utilized is Augmented Reality (AR). By employing Augmented Reality, it is possible to boost students' interest in the learning experience. In this study, the Action Research (PTK) method is employed to assess students' learning interest using AR technology.The research reveals an improvement in students' scores in the first cycle, with the initial cumulative score of 35% increasing to 40%. Chemistry is chosen as the subject for this study because students tend to achieve lower scores when working on assignments or exams without the integration of information technology in the instructional media.The study emphasizes the significance of incorporating technology, particularly Augmented Reality, to elevate students' learning experiences. In an era marked by the swift evolution of information technology, this research aims to bridge the gap between technological progress and the enhancement of students' learning interests.